Improving Elementary School Pupils' Chemical Literacy Using Context-Based Approach in Teaching the Unit Alkanes - Кatarina B. Putica; Lidija R. Ralević (University of Belgrade, Teacher Education Faculty, 2022)
Organic chemistry represents an essential part of everyday life, but previous research indicates that traditional organic chemistry teaching, which focuses on the transmission of academic content, insufficiently promotes the development of pupils' chemical literacy in this field. Since context-based teaching approach has the potential to improve scientific literacy, in order to compare the effectiveness of the aforementioned teaching approaches in terms of developing elementary school pupils' chemical literacy in the field of organic chemistry, a pedagogical experiment with parallel groups was conducted. The experiment was organized within the elaboration of the teaching unit Alkanes and it encompassed 148 eighth-grade elementary school pupils (76 pupils in the experimental and 72 pupils in the control group). Through the elaboration of the content about alkanes, pupils develop chemical literacy in regard to the structure and nomenclature of these compounds, their physical and chemical properties and oil and its derivatives as energy sources, as well as environmental pollutants. Upon the elaboration of the abovementioned teaching unit, the experimental group achieved a significantly higher overall percentage of correct answers on the test that checked the development of pupils' chemical literacy in regard to alkanes on all three levels (knowledge, application and reasoning), which implies that context-based teaching approach could significantly enhance elementary school pupils' chemical literacy, in the field of organic chemistry.